2003
DOI: 10.1093/bja/aeg034
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and gene expression in sepsis

Abstract: Dysregulation of the immuno-inflammatory response, as seen in sepsis, may culminate in host cell and organ damage. Lipopolysaccharide from Gram-negative bacterial cell walls induces gene activation and subsequent inflammatory mediator expression. Gene activation is regulated by a number of transcription factors at the nuclear level, of which nuclear factor kappaB appears to have a central role. The redox (reduction-oxidation) cellular balance is important for normal cellular function, including transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
294
0
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(319 citation statements)
references
References 105 publications
(86 reference statements)
10
294
0
15
Order By: Relevance
“…Similarly in the Adriamycin model of renal failure, renal cortex GPx activity was decreased to 69% of the control levels at 20 weeks after Adriamycin treatment Van den Branden et al (2000). These results also are in a harmony with the recorded data by Macdonald et al (2003) explained the oxidative stress occurs when a balance is disrupted by excessive production of Reactive Oxygen Speacies (ROS), including superoxide, hydrogen peroxide and hydroxyl radicals and/or by inadequate antioxidant defenses, including suboptimal levels of catalase, Glutathione Peroxidase (GPx), vitamins C and E and reduced glutathion. Sener et al (2004) found that in the erythrocytes of male Wistar albino rats at 4 weeks after 5/6 nephrectomy, GPx activity was found to be reduced, in addition Devinder et al (2004) found that the glycerol treated group showed depletion in antioxidant system which indicated by the significant decrease in the levels of glutathione reductase and superoxide dismutase enzymes.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly in the Adriamycin model of renal failure, renal cortex GPx activity was decreased to 69% of the control levels at 20 weeks after Adriamycin treatment Van den Branden et al (2000). These results also are in a harmony with the recorded data by Macdonald et al (2003) explained the oxidative stress occurs when a balance is disrupted by excessive production of Reactive Oxygen Speacies (ROS), including superoxide, hydrogen peroxide and hydroxyl radicals and/or by inadequate antioxidant defenses, including suboptimal levels of catalase, Glutathione Peroxidase (GPx), vitamins C and E and reduced glutathion. Sener et al (2004) found that in the erythrocytes of male Wistar albino rats at 4 weeks after 5/6 nephrectomy, GPx activity was found to be reduced, in addition Devinder et al (2004) found that the glycerol treated group showed depletion in antioxidant system which indicated by the significant decrease in the levels of glutathione reductase and superoxide dismutase enzymes.…”
Section: Discussionsupporting
confidence: 77%
“…SOD is a metallo-enzyme that catalyzes the dismutation of the superoxide anion (from oxidative phosphorylation, in ammation processes, ischemia, phagocytosis and in response to LPS and cytokines) to H2O2 [43]. is H 2 O 2 is later metabolized into water by glutathione peroxidase and catalase.…”
Section: Superoxide Dismutase (Sod)mentioning
confidence: 99%
“…Increased production of ROS accompanies inflammatory conditions, such as ischemiareperfusion injury and sepsis, and appears to contribute to organ system dysfunction in these settings (25,26). H 2 O 2 rapidly transits across cell membranes, and incubation of neutrophils and other cell populations with H 2 O 2 or the H 2 O 2 generating combination of glucose and glucose oxidase results in increased intracellular concentrations of H 2 O 2 , diminished 26 S proteasomal activity, and stabilization of cytoplasmic levels of proteins, such as IB-␣, that are normally degraded by the 26 S proteasome (27)(28)(29).…”
mentioning
confidence: 99%